The impact of an educational pain management booklet intervention on postoperative pain control after cardiac surgery. (January 2017) - Bjørnnes, Ann Kristin; Parry, Monica; Lie, Irene; Fagerland, Morten Wang; Watt-Watson, Judy; Rustøen, Tone; Stubhaug, Audun; Leegaard, Marit
Background: Relevant discharge information about the use of analgesic medication and other strategies may help patients to manage their pain more effectively and prevent postoperative persistent pain. Aims: To examine patients' pain characteristics, analgesic intake and the impact of an educational pain management booklet intervention on postoperative pain control after cardiac surgery. Concerns about pain and pain medication prior to surgery will also be described. Methods: From March 2012 to September 2013, 416 participants (23% women) were consecutively enrolled in a randomized controlled trial. The intervention group received usual care plus an educational booklet at discharge with supportive telephone follow-up on postoperative day 10, and the control group received only usual care. The primary outcome was worst pain intensity (The Brief Pain Inventory – Short Form). Data about pain characteristics and analgesic use were collected at 2 weeks and at 1, 3, 6 and 12 months post-surgery. General linear mixed models were used to determine between-group differences over time. Results: Twenty-nine percent of participants reported surgically related pain at rest and 9% reported moderate to severe pain at 12 months post-surgery. Many participants had concerns about pain and pain medication, and analgesic intake was insufficient post-discharge. No statistically significant differences between the groups were observed in terms of the outcome measures following surgery. Conclusion: Postoperative pain and inadequate analgesic use were problems for many participants regardless of group allocation, and the current intervention did not reduce worst pain intensity compared with control. Further examination of supportive follow-up monitoring and/or self-management strategies post-discharge is required.